A Review on Siwan Grass (Lasiurus scindicus) found in Arid Environments (International Journal of Food and Nutritional Sciences, 2022)
In particular, the Thar Desert in India is used in this review to highlight the significant function of Siwan grass (Lasiurus scindicus) in dry conditions. In order to deal with difficult temperatures and significant biotic pressure, it examines the ecological and economical advantages of agroforestry. Due to their ecological and practical benefits, indigenous plants are encouraged to be used in landscaping because of their capacity to adapt to dry environments. It also offers a thorough review of the vegetation of the Thar Desert, taking into account geology, climate, and interactions between people and plants. The article also explores the genetic diversity, phytochemical profile, and salt stress tolerance of Siwan grass. In conclusion, it emphasises the importance of grass in tackling climatic issues and resource constraints.